1997
DOI: 10.1128/iai.65.8.3422-3429.1997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of granulocyte and granulocyte-macrophage colony-stimulating factors in a neutropenic murine model of trichosporonosis

Abstract: We produced disseminated trichosporonosis in a neutropenic murine model with Trichosporon asahii, which was identified by DNA relatedness analysis. We then assessed the efficacy of granulocyte colony-stimulating factor (G-CSF) (30 to 100 g/kg of body weight per day) and granulocyte-macrophage colony-stimulating factor (GM-CSF) (0.8 to 2 g/kg ⅐ day). The administration of G-CSF either before or after infection improved the survival rate from less than 25% up to 100% (P < 0.05). The effects of G-CSF on organ cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 55 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, ex vivo incubation with G-CSF enhanced the impaired respiratory burst of neutrophils derived from transplant recipients against Candida and Cryptococcus yeasts as well as Aspergillus and Rhizopus conidia (Pursell et al, 2003). Treatment with G-CSF in neutropenic animal models of invasive candidiasis, aspergillosis or trichosporonosis was associated with faster recovery from neutropenia and improved survival (Hamood et al, 1994;Muranaka et al, 1997;Graybill et al, 1998). Recent studies, however, have demonstrated an additional important role of G-CSF in the regulation of adaptive T helper-cell responses.…”
Section: Cytokines and Antifungal Host Defencepreclinical Datamentioning
confidence: 99%
“…Furthermore, ex vivo incubation with G-CSF enhanced the impaired respiratory burst of neutrophils derived from transplant recipients against Candida and Cryptococcus yeasts as well as Aspergillus and Rhizopus conidia (Pursell et al, 2003). Treatment with G-CSF in neutropenic animal models of invasive candidiasis, aspergillosis or trichosporonosis was associated with faster recovery from neutropenia and improved survival (Hamood et al, 1994;Muranaka et al, 1997;Graybill et al, 1998). Recent studies, however, have demonstrated an additional important role of G-CSF in the regulation of adaptive T helper-cell responses.…”
Section: Cytokines and Antifungal Host Defencepreclinical Datamentioning
confidence: 99%
“…As described previously (25), three injections and aspirations with 10 mL of sterile ice-cold saline containing 1 mM EDTA were used to collect the BAL fluid in the rat. Cells from BAL fluid were determined by using a hemocytometer and differential cell counts were performed on 500 cells from BAL fluid with a modified Wright's stain.…”
Section: Bronchoalveolar Lavage (Bal) Fluid and Cell Countsmentioning
confidence: 99%
“…While TNF-a may enhance the host defence mechanisms against the invading microorganisms, previous studies have shown that large amounts of TNF-a released during the acute stages of infection may actually worsen the condition. In this regard, Muranaka et al [26] suggested that TNF-a overproduction in the lung has an important role in the prognosis of trichosporonosis. The peak concentrations of TNF-a in the plasma and bronchoalveolar lavage¯uid in their model at 24 h after infection were 742 6 104 pg/ml and 60´1 6 6´3 ng/ml, respectively.…”
mentioning
confidence: 99%